Design and maintenance of airport aprons: recommendations from thermomechanical analysis. (20th May 2021) - Martinez, Uliane Bortoloti; Calmon, João Luiz; Vieira, Darli; Bravo, Alencar
In this study, general recommendations for apron design are made by analysing the thermomechanical behaviour of concrete pavements under the effects of aircraft traffic and the environment. This analysis provides designers with data for decision-making on dimensioning to minimise maintenance costs throughout the pavement lifecycle. Pavement thermal differentials and stresses were compared for five Brazilian regions, as represented by the capitals Brasília, Manaus, Porto Alegre, São Paulo, and Teresina, considering the ambient temperature, solar radiation and typically-used coarse aggregate for each region. Parametric analyses for the pavement thermal differentials and stresses were also carried out. Thermal simulations were performed using a numerical model and ANSYS®/Multiphysic (Version 15.0) software, and structural simulations were performed using EverFE (Version 2.23) software. The resulting recommendations for the effective management of airport design provide clear guidance for the definition of metrics for managing apron pavement lifecycles.